PELAKSANAAN PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL KETENAGAKERJAAN DI YAYASAN PENDIDIKAN BEERSEBA HURIA KRISTEN BATAK PROTESTAN SUKAJADI KOTA PEKANBARU - JOHANES PASRA JAIMAN; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Social Security Administering Body is a legal entity established toorganize a social security program. The social security program is the BPJShealth program and the employment BPJS program. In this study, the authorsspecialize in the research of the BPJS Employment program. BPJS Manpower is alegal entity formed to organize a program of employment injury, pension, pension,and death insurance, where the program must be implemented for each employer.But in practice there are still employers who have not fulfilled their obligations toregister themselves and their employees to be participants of the BPJSEmployment program.In this case relate to the implementation of its obligations as an employerto register himself and his employees become participants of the program BPJSEmployment at the Foundation of Education Beerseba Huria Kristen BatakProtestant Sukajadi Pekanbaru City. The purpose of writing this thesis, namely:First, the implementation of the obligation of Beerseba Education FoundationHKBP Sukajadi Pekanbaru City against workers in the program of the EmployersSocial Security Employment Agency. Secondly, the efforts undertaken by BeersebaEducation Foundation HKBP Sukajadi Pekanbaru City against workers infulfilling the Program Organizer of Social Security Employment. This type ofresearch can be classified in the type of sociological juridical research, becausein this study the authors directly conduct research on the location or place understudy. This research was conducted at Beerseba Education Foundation HKBPSukajadi Pekanbaru City, while population and sample are all parties related tothe problem under study, data source used, primary data, secondary data, datacollection techniques in this study with questionnaires, interviews, and Literaturereview.From the results of research problems there are 2 main things that can beconcluded. Pertamai, the implementation of its obligations Yayasan as anemployer to give the right for every workforce to register its employees andthemselves become participants BPJS Employment program is not implemented inaccordance with applicable regulations. Second, the Foundation's ignorance ofthe presence of the Employment BPJS program for workers. Suggestion Writer,First, To the Government through Organ BPJS Employment should be betteragain to conduct supervision and more firmly again in giving sanctions fordisobedient performers. Second, the Party which is the employer's party should beaware of its obligation to fulfill the right that should be obtained by its workers.Keywords: Implementation - Social Security Program - BPJS Employment.